penelitian saya Aktualisasi Peran KUA dalam Pencegahan Pernikahan Dini akibat Kehamilan Pra Nikah Remaja: indonesia - Muhamad Ardianto; Akmam Mutrofin (Justicia Religia, 2026)
The phenomenon of early marriage resulting from premarital pregnancy among adolescents remains a social issue that requires serious attention from various parties, including the Office of Religious Affairs (KUA). This study aims to analyze the actual role of the KUA in efforts to prevent early marriage resulting from premarital pregnancy among adolescents in Gudo Subdistrict, Jombang Regency. This study employs a qualitative research method with an empirical-juridical approach. Data collection techniques were conducted through interviews, observations, and documentation involving the KUA, religious counselors, and relevant community members. The data obtained were analyzed descriptively through the stages of data reduction, data presentation, and drawing conclusions. Research findings indicate that the KUA plays a strategic role in preventing early marriage through religious counseling programs, premarital guidance, outreach on the legal marriage age, and support for adolescents and parents. In addition, the KUA also coordinates with community leaders and educational institutions to provide education on the negative impacts of early marriage. Nevertheless, prevention efforts still face several obstacles, such as low public awareness, the influence of promiscuity, as well as economic and educational factors. Therefore, strengthened collaboration between the KUA, families, schools, and the community is needed to reduce the rate of early marriage among adolescents.